Sportivnaya bor'ba: Dostizheniya, problemy, perspektivy - Ashkinazi, S. M. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Review of the contents of new book (1999) by prokhorovoi, Semenova and Posishkova: " Ringen: Erreichtes, Probleme, Perspektiven".